Romanian Wellness Tourism – A Potential Solution with Positive Implications for the Effects of the Aging Population in the European Union - Alina-Cerasela Aluculesei; Puiu Nistoreanu (Amfiteatru Economic)
Romania is a member state of the European Union. Among the resources of the Romanian tourist patrimony, mineral and thermal waters, mofettes, salt mines, muds and the climate build up a valuable portfolio of the wellness tourism offer. These resources are used to recover and reacquire the strength to work, but also for minimizing the effects of degenerative diseases commonly affecting senior citizens. The aging of the population of the European Union is one of the challenges affecting this block on a macroeconomic level increasingly more visibly. A solution for minimizing the effects of the rising number of senior citizens might be the integration of the Romanian wellness offer in the European tourist offer. Our country is also affected by this phenomenon and the existing wellness resources are useful in diminishing the negative effects of the aging process. The research began by analyzing the specialized literature, which confirmed the phenomenon of aging among the Europe's population. This was followed by a pilot study (287 respondents) which was undertaken from June to December 2015 on representatives of the Romanian population. Romania's tourist heritage, represented by its wellness tourism resources, may represent an important tourist product on the European market which can help senior citizens benefit from treatments of degenerative illnesses.